Positioning Law and Ethics as an Effort to Minimize Election Administrative Violations - Jeremia Alexander Wewo (Universitas Islam Negeri Alauddin Makassar, 2023)
Data on violations of the 2019 General Election, there is a very significant number of administrative violations of the General Election. The research method used is normative legal research. The findings in the research results are that law and ethics in the General Election stage are an inseparable part. The law that is used as a foothold in the General Election stage cannot stand without the presence of ethics because the formation of law must be based on ethical values. The position of law in minimizing administrative violations of the General Election consists of the position of law as a means of application of values contained in society and a means of orders, prohibitions, and sanctions that are firm and clear while ethics is present as a means of assessing actions, a means of assessing legal language, and a means of determining decisions on sanctions given.